F(x)=6x2+6x-1

Simple and best practice solution for F(x)=6x2+6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=6x2+6x-1 equation:



(F)=6F^2+6F-1
We move all terms to the left:
(F)-(6F^2+6F-1)=0
We get rid of parentheses
-6F^2+F-6F+1=0
We add all the numbers together, and all the variables
-6F^2-5F+1=0
a = -6; b = -5; c = +1;
Δ = b2-4ac
Δ = -52-4·(-6)·1
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-7}{2*-6}=\frac{-2}{-12} =1/6 $
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+7}{2*-6}=\frac{12}{-12} =-1 $

See similar equations:

| 5+4(2x+3)=2x-3 | | 16+3k=4k | | x+2/2=5/6+x+3/3 | | 2/3y+6=2/3+6 | | -34=s/4 | | X/2=5x/6+1/9 | | 4m-7=18/2 | | 7+y=31/4 | | 3(x+4)=-(x-5) | | (3/5)w-(1/5)w+10=4 | | 4c=3c-10 | | (3/5)w-(1/5)+10=4 | | 4x-13+3x=7+7x-20 | | F(x)=-2x^+4x+1 | | 8x/9-1/9=23/9-4x-9 | | (3/5)w-(1/5)w+19=4 | | 1/x+5/x-9=0 | | 1,1x-0,9=0,4x-0,5 | | 2g-2=8/2g-3 | | x-13/3=-6 | | .3t+1.4=4.2-0.1t | | 4.9t^2+10t=3.5 | | 2z-30=2(z-15) | | 10+7m=3(2m+5)+m | | 9x-8x=-9 | | (1/2x)+7=(3/4x)-4 | | (5^k)^3=(^3÷5)^3 | | a•164363-10=10 | | -20-3p=10 | | x-17/11=-2 | | 6-2(x+6)=3x+4= | | 5x+2=12x+19 |

Equations solver categories